Pengaruh Digital Competence, Fear of Missing Out (Fomo), dan Peer Pressure terhadap Keputusan Pembelian melalui Literasi Keuangan sebagai Variabel Mediasi pada Gen Z Kota Malang - Naili Ifrozul Mawaddah; Cipto Wardoyo; Ludi Wishnu Wardana (Universitas Hamzanwadi, 2026)
The rapid development of digital technology has significantly changed consumer behavior, particularly in purchase decision-making among Generation Z. As a generation that grows and interacts within a digital environment, Generation Z shows high intensity in using digital platforms and e-commerce. This condition requires adequate digital competence and financial literacy to support rational consumption behavior. At the same time, psychological and social factors such as fear of missing out (FOMO) and peer pressure also influence purchasing tendencies, often leading to impulsive buying behavior. This study aims to analyze the effects of digital competence, fear of missing out (FOMO), and peer pressure on purchase decisions, both directly and indirectly through financial literacy as a mediating variable. A quantitative research approach was employed using a survey method. Data were collected from Generation Z respondents who had experience with online shopping. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine direct and indirect relationships among the variables. The results indicate that digital competence has a positive and significant effect on financial literacy and purchase decisions. Meanwhile, FOMO and peer pressure do not have a significant direct effect on purchase decisions; however, both variables significantly influence financial literacy. Furthermore, financial literacy has a positive and significant effect on purchase decisions. Mediation analysis confirms that financial literacy plays an important role in mediating the effects of digital competence, FOMO, and peer pressure on purchase decisions. These findings highlight the strategic role of financial literacy in controlling the influence of digital, psychological, and social factors on consumer behavior. Therefore, strengthening financial literacy and digital competence is essential to encourage rational and responsible purchasing decisions among Generation Z in the digital era.